BARRIERS TO ADVANCED HERITAGE LANGUAGE DEVELOPMENT - Ashtari, Nooshan; Krashen, Stephen (LLT Journal: A Journal on Language and Language Teaching, 2023)
Speakers of heritage languages do not universally achieve advanced levels in the language. We present evidence that three barriers are responsible: (1) lack of access to comprehensible, interesting reading material in the heritage language. (2) The use of traditional language teaching methods in heritage language classes, and (3) the reactions of elders who scold young heritage language speakers for their “errors.”